Classification of Gurkani and Safavid Fabrics’ Motifs According to the Impact of Persian Art on the Region - Mirmobini, Niaz; Narani, Hanieh Sheikhi (Journal of History Culture and Art Research, 2021)
Fabrics and the use of patterns in the textile industry have undergone countless and astonishing changes due to the biological climate, the degree of civilization and culture, religious beliefs and customs. The study of the evolution of clothing and various fabrics is not only important from the point of view of history and art, but also from the point of view of sociology and understanding of the nations’ psychology. The history of patterns is the same as the history of textiles and clothing, so it can be examined directly and indirectly from a conceptual and thematic point of view. Comparing the patterns and designs of Indian Gurkani fabrics with the textiles and artworks of Safavid Iran shows that Indian weavers have created works under the influence of Iranian art that is difficult to distinguish from each other. Due to the many impacts of Iranian art in many designs, the Gurkani have consciously tried to localize the used patterns and motifs, such as the altar pattern. A variety of motifs, including decorative, plant, animal, and pictorial arrays, have been used in Gurkani Indian fabrics, which have undoubtedly been greatly influenced by the Iranians according to the conditions of the time. The main purpose of this research is to classify the patterns of Safavid and Gurkani fabrics and the main focus of the research is the woven designs and patterns in Safavid and Gurkani fabrics. Accordingly, by classifying the designs and patterns, the level and extent of their impact on each other have been studied and plant, human, animal and calligraphic motifs have been studied comparatively.